2019
DOI: 10.3390/agriculture9080174
|View full text |Cite
|
Sign up to set email alerts
|

Quality Determinants and Effect of Therapeutic Properties in Honey Consumption. An Exploratory Study on Italian Consumers

Abstract: Nowadays, more and more consumers show a growing interest in healthy food products that may help to maintain or improve human health, such as honey. Honey has always represented a fundamental component of traditional medicine in many world cultures. However, only thanks to several studies carried out in the last years, its use is considered as an alternative and complementary medicine, namely apitherapy. In this way, honey is recognized increasingly by consumers not only as a natural alternative to refined sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 70 publications
(78 reference statements)
4
39
0
9
Order By: Relevance
“…In most of the literature explored, honey consumer attitudes and preferences are linked to extrinsic and sensory attributes (Arvanitoyannis and Krystallis, 2006;Batt and Liu, 2012;Cosmina et al, 2016), in addition to the uses and motivations related to health benefits (Br s ci c et al, 2017;Ismaiel et al, 2014;Testa et al, 2019) or environmental sustainability (Arvanitoyannis and Krystallis, 2006;Jensen and Mørkbak, 2013). In addition, other authors (Jones Ritten et al, 2019;Kallas et al, 2019;Schifani et al, 2016) have supported the role of geographical proximity, by analysing the consumer drivers for locally produced honey.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the literature explored, honey consumer attitudes and preferences are linked to extrinsic and sensory attributes (Arvanitoyannis and Krystallis, 2006;Batt and Liu, 2012;Cosmina et al, 2016), in addition to the uses and motivations related to health benefits (Br s ci c et al, 2017;Ismaiel et al, 2014;Testa et al, 2019) or environmental sustainability (Arvanitoyannis and Krystallis, 2006;Jensen and Mørkbak, 2013). In addition, other authors (Jones Ritten et al, 2019;Kallas et al, 2019;Schifani et al, 2016) have supported the role of geographical proximity, by analysing the consumer drivers for locally produced honey.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the consumption behavior of honey show that the frequency of consumption is lower among young consumers compared to older generations, emphasizing the need for better promotion of bee products among this age segment (Testa et al, 2019;Pidek, 2001; Pocol and Bolboacă, 2013). Popescu and Guresoaie (2019) observed that the 36-50 age group, followed by the 51-65 one are the most loyal consumers of honey, regardless of quantity.…”
Section: Honey Consumption Among Young Generationsmentioning
confidence: 99%
“…As for common consumer products with amber-colored liquids such as cooking oil, honey, maple syrup and beer, consumers evaluate the color of the product apart from the product packaging, price and label information [ 33 ]. The color of these amber-colored liquid products is highly related to its content, flavor and taste.…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, the color of the honey and maple syrup also plays an important role in the market price of the products [ 35 ]. Appropriate color measurement allows exporters and producers to choose the most beneficial trading market for their products [ 33 , 36 ]. However, general consumer preferences toward the color of amber-colored liquid are still inconclusive.…”
Section: Introductionmentioning
confidence: 99%